EFEKTIVITAS TERAPI ZIKIR DALAM MENURUNKAN TINGKAT KECEMASAN PADA INDIVIDU MENGHADAPI TANTANGAN HIDUP - Amelya, Tiska Dwi (JIP (Jurnal Intervensi Psikologi), 2025)
ABSTRACT: Severe life challenges such as coming from a broken home family, losing a job, or experiencing difficult economic conditions can trigger significant anxiety in individuals. This study aims to determine the effectiveness of dhikr therapy in reducing anxiety levels in individuals facing life challenges. The study used a quasi-experimental method with a pretest-posttest control group with follow-up design. The research sample involved 14 people who were divided into experimental groups (n = 7) and control groups (n = 7). Measurements used the Hospital Anxiety and Depression Scale (HADS) to measure changes in anxiety levels. The intervention provided refers to the Zikr Therapy Module developed by researchers, which is structured in 3 meetings with a total of 12 sessions. Data were analyzed using Anova Mixed Design. The results showed that dhikr therapy was effective in reducing anxiety levels in individuals facing life challenges with an effective contribution of 82%. These findings provide  a foundation for the development of religious-based psychological interventions to overcome anxiety problems in individuals who face various severe life challenges. Key words: Anxiety, dhikr therapy, life challenges, psychological interventions. ABSTRAK: Tantangan hidup yang berat seperti berasal dari keluarga broken home, kehilangan pekerjaan, atau mengalami kondisi ekonomi sulit dapat memicu kecemasan yang signifikan pada individu. Penelitian ini bertujuan untuk mengetahui efektivitas terapi zikir dalam menurunkan tingkat kecemasan pada individu yang menghadapi tantangan hidup. Penelitian menggunakan metode kuasi-eksperimen dengan pretest-posttest control group with follow up design. Sampel penelitian melibatkan 14 orang yang dibagi menjadi kelompok eksperimen (n=7) dan kelompok kontrol (n=7). Pengukuran menggunakan skala Beck Anxiety Inventory (BAI) untuk mengukur perubahan tingkat kecemasan. Intervensi yang diberikan mengacu pada Modul Terapi Zikir yang disusun oleh peneliti secara terstruktur dalam 3 pertemuan dengan total 12 sesi. Data dianalisis menggunakan Anova Mixed Design. Hasil penelitian menunjukkan bahwa terapi zikir efektif dalam menurunkan tingkat kecemasan pada individu yang menghadapi tantangan hidup dengan sumbangan efektif sebesar 82%. Penelitian ini dapat menjadi dasar pengembangan intervensi psikologis berbasis religius untuk mengatasi masalah kecemasan pada individu yang menghadapi berbagai tantangan hidup berat. Kata kunci: Intervensi psikologis, kecemasan, tantangan hidup, terapi zikir.